Optimization of Si/ZnO/PEDOT:PSS tri-layer heterojunction photodetector by piezo-phototronic effect using both positive and negative piezoelectric charges. (June 2018) - Li, Fangpei; Peng, Wenbo; Pan, Zijian; He, Yongning
Abstract: Piezo-phototronic effect has been extensively introduced to improve the performances of optoelectronic devices by utilizing external-strain-induced positive or negative piezoelectric charges (piezo-charges) to modulate the generation, separation, transportation, and recombination of charge carriers. However, in most cases till today, only the piezo-charges with one polarity ( i.e., positive or negative) are effectively utilized. In this work, we fabricated an n-Si/n-ZnO/p-PEDOT:PSS tri-layer heterojunction photodetector (HPD) and systematically investigated the piezo-phototronic effect on its performances simultaneously utilizing both positive and negative piezo-charges for the first time. The photoresponsivity to 405 and 648 nm laser illuminations can be gigantically optimized, with astonishing enhancement of over 3000% and 1800% compared to that under strain free condition, respectively. The in-depth working mechanisms is systematically investigated by carefully analyzing the strain-induced variations in energy band diagrams of the HPD, which is further validated by finite element analysis simulations. This work not only presents the utilization of both positive and negative piezo-charges to optimize the performances of HPD by the piezo-phototronic effect, but also provides a deep understanding of how the piezo-charges of two opposite polarities work together in one optoelectronic device, hopefully proposing the idea of introducing the piezo-phototronic effect into three-/multi-layer devices in future applications. Graphical abstract: fx1 Highlights: The piezo-phototronic effect using both positive and negative piezo-charges in one device is studied for the first time. A tri-layer photodetector is fabricated and the piezo-phototronic effect on its photoresponse is investigated. Gigantic photoresponse performance improvement is achieved. Working mechanism is analyzed, revealing the combined modulation by piezo-charges of both polarieties.